Effect of Creatine Supplementation on Body Composition in Cancer Patients: A Systematic Review. - del Arco, Asier; Aguirre-Elordui, Saioa; Olasagasti-Ibargoien, Jurgi; Castañeda-Babarro, Arkaitz (Nutrition & Cancer, 2025)
Creatine is a naturally occurring compound stored in muscles, obtainable through diet and supplementation, known to enhance strength, exercise capacity, and recovery. Recent research suggests it may aid in treating some chronic diseases. This review analyzed the effects of creatine supplementation (CrS) on body composition in cancer patients or survivors. Following PRISMA guidelines, five databases were searched for studies up to September 12, reviewing seven articles with 463 participants (316 men, 147 women; average age 62.95 years). Five studies assessed CrS effects on body weight: three found no changes, while two reported increases. For lean body mass, three trials noted increases in both creatine and placebo groups, but differences were not significant. Fat mass results varied, showing reductions, no changes, or mitigated increases during hormone therapy. Although CrS showed potential improvements, evidence of significant effects on body composition in cancer patients remains limited. CrS appears safe and might be more beneficial with less aggressive treatments or in non-metastatic cases. Further research is needed to clarify its role in this context.